Design of a home-based elderly service robot using ROS - Zhao Zebei; Feng Peilin; Xie Xiaorui; Zhang Jing (Dianzi Jishu Yingyong, 2025)
Addressing the current issues with elderly service robots, such as limited intelligent voice functions, insufficient perception capabilities, and low integration levels, this paper designed a robot with features including facial recognition, voice interaction, and fall detection. The robot is developed on the Robot Operating System (ROS) platform, equipped with a Jeston Nano main control board, a ZED2i stereo camera, and various other sensors. By employing facial recognition based on Haar features and LBPH algorithm, voice interaction using Alpaca-2 model, and fall detection based on ZED2i stereo camera, it provides more comprehensive and intelligent care services for the elderly. Experimental results demonstrate excellent performance of the robot in facial recognition, voice interaction, and fall detection.